The effect of lower-limb wearable resistance on anterior pelvic tilt during high-speed running: A pilot study - Feser, E.; Sabin, D. (ISBS Proceedings Archive (Michigan), 2023)
This study determined the effect of two different lower-limb wearable resistance loads on anterior pelvic tilt during high-speed (4.72 - 6.71 m/s) treadmill running. Nine athletes completed a series of 10-second intervals at a self-selected speed for each experimental condition. Compared to unloaded running, the heaviest wearable resistance load (0.91 - 1.24 kg) significantly (p < 0.05) reduced anterior pelvic tilt at the instants of maximal hip extension and maximal hip flexion by -3.54° (ES = 0.80) and -3.30° (ES = 0.55), respectively. Individual responses showed a primary trend towards a reduction in anterior pelvic tilt when running with wearable resistance (6/9 athletes). This study provides initial evidence for the use of lower-limb wearable resistance as a training stimulus to induce pelvic kinematic changes over time.